Relativism, pluralism and the interpretation of cultures - Fermandois, Eduardo (Estudios de Filosofía, 2008)
It is still peculiar that despite the notorious commotion generated by relativism -relativism, thus without surnames-, the judgments regarding its effective presence vary from one extreme to another: from the Rortian suspicion that there has never been any relativist to the concern of the current Pope, who not for nothing coined the expression "dictatorship of relativism." Ghost or epidemic: there are philosophers who, without going as far as Rorty, tend to the first diagnosis; there are others who, without being as concerned as the Pope, are concerned. Thus, relativism generates an adhesion that is not at all evident, despite the noise it evidently generates. People talk and talk about the relativist, but either they criticize him loudly, or defend him with a mute, the truth is that we do not know for sure who is criticized or defended. "Relativism" is the name of a point of view held by someone who has no name. [Fragment]